Strategi Personal Branding Kreator Media Sosial untuk Membangun Visibilitas, Kredibilitas, dan Keberlanjutan dalam Creator Economy - Reski; Farida Febriati (STKIP Subang, 2025)
This study aims to analyze how social media creators build and manage personal branding strategically to achieve visibility, credibility, and sustainability in the creator economy. The method used is a Systematic Literature Review (SLR) based on the PRISMA protocol, by selecting 10 relevant articles from the Scopus database. The results show that personal branding is a multidimensional process that involves identity construction, the use of platform algorithms, and the management of relationships with the audience. Creators build differentiation through the exploration of self-values, narrative consistency, and the strengthening of authenticity, while algorithms act as architects of visibility that determine reach and monetization opportunities. The study also reveals dilemmas between authenticity and commercialization, algorithmic bias, and forms of platform control that affect creators’ strategies. To maintain sustainability, creators develop strategies such as income diversification, cross-platform presence, and community strengthening. This study contributes to the theoretical understanding of creators’ personal branding strategies in the digital ecosystem and provides practical implications for creators and platform developers in creating a more fair and sustainable environment